2017
DOI: 10.1142/s0217979217450187
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ZnO doping on the properties of single domain YBCO bulks fabricated by RE+011 TSIG process

Abstract: Single domain YBCO bulk superconductors with different additions of ZnO have been successfully fabricated by RE+011 TSIG process with a new solid phase of [(100 − x)(Y 2 O 3 +1.2BaCuO 2 )+xZnO] and a new liquid phase of (Y 2 O 3 +6CuO+10BaCuO 2 ). The effects of ZnO additions on the growth morphology, microstructure, critical temperature (Tc), the levitation force and trapped field of the YBCO bulks have been investigated. It is found that within the range of ZnO additions x = 0-1.0 wt.%, all the samples are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is possible to produce large single-grained samples aligned in the c-axis direction with the melting methods and especially top seed melt growth (TSMG) and infiltration growth (IG) methods are promising. Generally, seeds having a higher melting temperature and a similar crystal structure to the main sample are used in these methods [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to produce large single-grained samples aligned in the c-axis direction with the melting methods and especially top seed melt growth (TSMG) and infiltration growth (IG) methods are promising. Generally, seeds having a higher melting temperature and a similar crystal structure to the main sample are used in these methods [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…González et al also presented the enhancement of J c by ZnO doping, and found that ZnO doping with the amount up to 0.6% will not significantly affect the size and distribution of Y211 particles [33]. Yang et al fabricated bulks by RE + 011 TSIG process and obtained increment of 21.1% and 30.4% in levitation force and trapped field respectively when 0.1 wt% ZnO was added to YBCO at 77 K [34].…”
Section: Introductionmentioning
confidence: 99%